Implications of Digitalisation on Skill Needs in a Sustainable Economy - Monica Mihaela Maer Matei; Cristina Mocanu; Ana Maria Zamfir; Anamaria Nastasa (Amfiteatru Economic, 2023)
Digitalisation and mainly artificial intelligence led to significant disruptions at all levels of society, changing how we live, communicate, build communities, work, and learn. In addition, digital technologies offer solutions to achieve sustainable development goals. Therefore, to benefit from this potential, it is vital to understand the skill needs associated with sustainable digitalisation. The impact of digitisation on the labour market is largely documented, but there are still important debates on what future jobs will look like. On the one hand, some scenarios announce massive shifts and destruction of jobs with rhythms that cannot be managed well by societies, while others point instead to transformations of skills needs. Therefore, our article aims to investigate the links between digitalisation and skills needs among digitalised enterprises, focussing on those implementing artificial intelligence solutions. In this respect, we use various multivariate techniques to analyse the data made public for the Flash Eurobarometer 486 (2020). Our findings suggest that digitalisation leads to skills shortages and skill gaps among companies adopting different digital solutions. In other words, digitalisation requires more workers with better digital skills.
Keywords: C30; D22; 330; Digital transformation; skills needs; skills shortage; sustainable digital economy.